trans-3,3′,4,5′-Tetramethoxystilbene - Ri-An Yan; Xiao-Xia Li; Guo-Qiang Li (Acta Crystallographica Section E, 2011)
The title compound, C18H20O4, was synthesized by a Wittig–Horner reaction of diethyl 3,4-dimethoxybenzylphosphate and 3,5-dimethoxybenzaldehyde. In the crystal, the dihedral angle between the two aromatic rings is 2.47 (12)°. All the methoxy groups are almost coplanar with the aromatic ring to which they are attached [C—C—O—C torsion angles = −2.8 (3), −5.2 (4), −176.3 (2) and −178.0 (2)°].